2014
DOI: 10.1039/c4ce00054d
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation mechanism of GaN growth on wet etched pattern sapphire substrates

Abstract: Patterned sapphire substrates (PSS) are generally applied and have been proved to be effective in the increasing light extraction efficiency and crystal quality of GaN-based LEDs. The time evolution growth of GaN on triangle platform shaped PSS with an n-plane inclined surface and triangle cone shaped PSS with a part r-plane surface has been performed to research the nucleation and 3D growth mechanisms of GaN grown on the PSS. After the low temperature GaN growth process and high temperature ramping process, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…The 3D growth of AlN and transition to AlGaN, after 5000 s, exhibits the priority growth characteristics on the inclined and top surface of the coneshaped PSS (c-and n-plane sapphire), but not on the bottom surface, due to the early contact with the growth atmosphere. The nucleation mechanism and growth habit of such scenario were observed in GaN and explained by Sun et al [31]. A selective nucleation phenomenon observed in the growth process of GaN was explained on differently shaped PSS platform, proving that there are distinct preferable crystallographic growth directions during GaN 3D growth.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The 3D growth of AlN and transition to AlGaN, after 5000 s, exhibits the priority growth characteristics on the inclined and top surface of the coneshaped PSS (c-and n-plane sapphire), but not on the bottom surface, due to the early contact with the growth atmosphere. The nucleation mechanism and growth habit of such scenario were observed in GaN and explained by Sun et al [31]. A selective nucleation phenomenon observed in the growth process of GaN was explained on differently shaped PSS platform, proving that there are distinct preferable crystallographic growth directions during GaN 3D growth.…”
Section: Resultsmentioning
confidence: 84%
“…A selective nucleation phenomenon observed in the growth process of GaN was explained on differently shaped PSS platform, proving that there are distinct preferable crystallographic growth directions during GaN 3D growth. It was found that due to the asymmetric surface tension underneath the GaN nucleus, after ramping from low to high temperature during GaN growth process, the small islands of GaN rotate and gather on n-plane surface, resulting in a 3D behavior [31]. Thus, separated hexagonal platform shape pillars can be grown by a careful control of process parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The closepacked hexagonal array further enhances the light output because of a large fill factor. 17 Besides this, the top C-planes and sidewall facets outside the truncated pyramid provide more GaN nucleation sites, 21 which facilitate the epitaxy of GaN. The etching {11 ¯08} facets will appear when etched by a H 2 SO 4 /H 3 PO 4 mixture at 270 °C using a ring-array SiO 2 mask for sufficient etching time.…”
Section: Resultsmentioning
confidence: 99%
“…A truncated pyramid PSS with GaN buffer gathering near its ridges showed the 3D growth mechanism of GaN. 21 To sum up, the optimized pattern of the PSS is a critical factor for the enhancement of light output power in GaN-based LEDs.…”
Section: Introductionmentioning
confidence: 97%
“…5 The mechanism of the GaN initial growth stages on micro-PSS has been reported by some groups. 15,16 However, there are few reports about the initial growth process for NPSS. It is found that the surface energy of the sapphire substrates is altered by nano patterns.…”
Section: Introductionmentioning
confidence: 99%